Understanding the Resistance to Health Information Systems - David Ackah; Angelito E Alvarado; Heru Santoso Wahito Nugroho; Sanglar Polnok; Wiwin Martiningsih (Humanistic Network for Science and Technology (HNST), 2017)
User resistance is users’ opposition to system implementation. Resistance often occurs as a result of a mismatch between management goals and employee preferences. There are two types of resistance to health iformation system namely active resistance and passive resistance. The manifestation of active resistance are being critical, blaming/accusing, blocking, fault finding, sabotaging, undermining, ridiculing, intimidating/threatening, starting rumors, appealing to fear, manipulating arguing, using facts selectively, distorting facts and raising objections. The manifestation of passive resistance are agreeing verbally but not following through, failing to implement change, procrastinating/dragging feet, feigning ignorance, withholding information, suggestions, help or support, and standing by and allowing the change to fail. Keywords: Health information systems, User Resistance, Active resistance, Passive resistance